2019
DOI: 10.1055/s-0039-1697767
|View full text |Cite
|
Sign up to set email alerts
|

Viral Encephalitis: A Hard Nut to Crack

Abstract: Viral encephalitis is inflammation of brain that manifests as neurological complication of viral infections. There are quite a good number of viruses, for example, human herpes virus, Japanese encephalitis, and enteroviruses that can result in such a dreadful condition. Geographical location, age, gender, immune status, and climatic conditions also contribute to the establishment of this disease in an individual. Clinical signs and symptoms include fever, headache, altered level of consciousness, changed menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 108 publications
(189 reference statements)
0
2
0
Order By: Relevance
“…The results of this study showed that the GMFM-88 score was higher in the early intervention group than in the late intervention group after 4 weeks of intervention. From the perspective of functional recovery (18), the early abnormal motor pattern has not yet been established, and brain function development during this period exhibits strong plasticity (19). Therefore, gradually increasing exercise and continuously providing benign stimulation to children with acute VE during this period can stimulate the repair of their central nervous system (20), thus promoting the recovery of motor function.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the GMFM-88 score was higher in the early intervention group than in the late intervention group after 4 weeks of intervention. From the perspective of functional recovery (18), the early abnormal motor pattern has not yet been established, and brain function development during this period exhibits strong plasticity (19). Therefore, gradually increasing exercise and continuously providing benign stimulation to children with acute VE during this period can stimulate the repair of their central nervous system (20), thus promoting the recovery of motor function.…”
Section: Discussionmentioning
confidence: 99%
“…ST is often considered as occupational disease of rural population since the chances for exposure to infected chiggers are higher in rural areas (4).This disease usually exhibits a spectrum of the signs and symptoms including pyrexia (may or may not with chills), headache, myalgia body-ache, nausea, vomiting, abdominal pain, non-pruritic macular or maculo-papular rash (not always), eschar, and a pathognomonic sign of ST which is a dark scab like lesion at the site of bite (sometimes goes unnoticed) (5). However, other symptoms such as enlarged lymph nodes and alteration in mental status ranging from confusion and encephalitis to coma have been also reported (1,3,5,6).…”
mentioning
confidence: 99%